Presença de peróxidos em rações e a ocorrência de miopatias em frangos de corte - Calasans, Max Weber de Menezes (2017)
The rations provided to broilers have oil and fat with a high amount of unsaturated fatty acids that are susceptible to oxidation reactions influenced by several factors such as composition of fatty acids, oxygen concentration, moisture, heat, light, presence of metals and Lipoxygenase. In this research, ferric chloride was the chemical selected to cause controlled peroxidation in poultry feed and, consequently, to cause degradation of selenium, fat soluble vitamins such as K and E, as well as amino acids and lipids. These components would be responsible for the development of hemorrhagic disorders, muscular dystrophies, necrosis and fibroses associated with myopathies of the chicken of origin of idiopathic such as Deep Pectoral Myopathy, White Striping, Wooden Breast and Dorsal Cranial Myopathy. To evaluate this hypothesis two experiments were performed, totaling 480 male broilers of the Cobb Slow line, divided into four replicates. The birds were placed in 16 boxes with 15 birds each, divided into four experimental groups in an aviary located in the city of Passo Fundo - RS, where the conventional broiler chicken feed was added with ferric chloride in order to develop controlled peroxidation. The first experiment was carried out with the following treatments: Group 1: without addition of ferric chloride; Group 2: 1 mL of ferric chloride per 1 kg of feed; Group 3: 4 mL / 1 kg and Group 4: com, 8 mL / 1 kg. In the second experiment the following concentrations were used: Group 1: without addition of ferric chloride; Group 2: 4 ml of ferric chloride / kg / feed; Group 3: 8 mL CF / kg / serving and Group 4: 12 mL CF / kg / serving. At 42 and 49 days old, respectively, the birds of the first and second experiments were slaughtered in a refrigerator under Federal Inspection and the occurrence of these myopathies was evaluated. In the first experiment, of the 240 slaughtered animals, 180 were inspected due to the rupture of the seals during processing and, of this total, 89 (49.4%) presented myopathies. Among the 89 carcasses, 61 (68.53%) were WS, 9 (10.11%) WB, 18 (20.22%) presented both lesions in the same carcass and only one (1.12% ) Presented WS, WB and MPP simultaneously. Already 91 (50.55%) of the evaluated carcasses did not present myopathies. In the second experiment, with 240 birds, four died in the breeding phase and 22 seals were ruptured in the slaughtering process. Twenty-four carcasses were inspected in 137 (64%), of which 16 (7.47%) were WB , 26 (12.14%) WS, 95 (44.39%) presented both lesions simultaneously and 77 (35.98%) without myopathies. The ration consumed with a high peroxide index by broilers caused a higher occurrence of WB and WS, but this is not an isolated factor for myopathies, and variables such as genetics and environment also favor the triggering of this complex pathology. On the other hand, MPP and MDC myopathies were not related to the consumption of oxidized ration.